Primary Brain Tumor Research Productivity in Southeast Asia and Its Association With Socioeconomic Determinants and Burden of Disease - Mondia, Mark Willy L.; Espiritu, Adrian I.; Jamora, Roland Dominic G. (Frontiers in Oncology, 2020)
Background: There is an unmet need to assess research productivity from southeast Asia (SEA) regarding primary central nervous system (CNS) tumors. The country’s economy, landscape of neurology practice, and disease burden are hypothesized to correlate with scientific output. This study aimed to objectively measure the impact of published studies on primary brain tumors in SEA and to assess for correlation with socioeconomic determinants and burden of disease. Methods: We systematically searched electronic databases for relevant articles from SEA on primary CNS tumor until July 31, 2020. Bibliometric indices were reported and subjected to correlational analysis with population size, gross domestic product (GDP) per capita, percentage (%) GDP for research and development (R&D), total number of neurologists, disease incidence, deaths, and disability-adjusted life years. Results: A total of 549 articles were included, consisting primarily of case reports (n=187, 34.06%) and discussed gliomas (n=195, 35.52%). Singapore published the most number of the articles (n=246, 44.8%). Statistical analysis showed a positive correlation between %GDP for R&D and total publication. Additionally, negative relationships were noted between burden of disease and total neurologist with most bibliometric indices. However, GDP per capita was not correlated with measures for research productivity. Conclusion: The low impact of scientific output on primary CNS tumors in SEA does not address the growing epidemiology and burden of this disease. An increase in the GDP growth and financial and manpower investment to R&D may significantly improve research productivity in SEA.